Purified recombinant hARD1 does not catalyse acetylation of Lys532 of HIF-1alpha fragments in vitro. - Murray-Rust, T; Oldham, N; Hewitson, K; Schofield, C (2006)
In humans, many responses to hypoxia including angiogenesis and erythropoiesis are mediated by the alpha/beta-heterodimeric transcription factor hypoxia inducible factor (HIF). The stability and/or activity of human HIF-1alpha are modulated by post-translational modifications including prolyl and asparaginyl hydroxylation, phosphorylation, and reportedly by acetylation of the side-chain of Lys532 by ARD1 (arrest defective protein 1 homologue), an acetyltransferase. Using purified recombinant human ARD1 (hARD1) we did not observe ARD1-mediated N-acetylation of Lys532 using fragments of HIF-1alpha. However, recombinant hARD1 from Escherichia coli was produced with partial N-terminal acetylation and was observed to undergo slow self-mediated N-terminal acetylation. The observations are consistent with the other data indicating that hARD1, at least alone, does not acetylate HIF-1alpha, and with reports on the N-terminal acetyltransferase activity of a recently reported heterodimeric complex comprising hARD1 and N-acetyltransferase protein.